Etnomatemática na educação escolar quilombola : perspectivas decoloniais para o ensino da matemática nos quilombos Mata Cavalo e Abolição em Mato Grosso - Silva, Maria do Socorro Lucinio da Cruz (2022)
This thesis is a part of the collective project of the Study and Research Group on Quilombola Education, coordinated by Professor Dr. Suely Dulce de Castilho and entitled: Etnossaberes: perspectiva e desafios para formação de professores atuantes em Educação Escolar Quilombola (Etnossaberes: perspective and challenges for the working training of teachers in Quilombola School Education). Its objective was to describe and analyze the training processes of mathematics teachers from two quilombola schools in Mato Grosso, based on the assumptions of Ethnomathematics, and the impacts of this training on their teaching practices. The locus of the research was the quilombola schools of the Mato Grosso education system: Escola Estadual Quilombola Professora Tereza Conceição Arruda, located in the Mata Cavalo quilombola community, and Escola Estadual Quilombola Maria de Arruda Muller, located in the Abolição quilombola community. The participants of the research were four mathematics teachers, working in both schools. The theoretical discussion covered the concepts of quilombo, Quilombola School Education, curriculum, Eurocentrism and decolonial theories, presuppositions of Ethnomathematics and teacher's education, as well as the Curricular Guidelines and Orientations for Quilombola School Education. To this end, a dialogue was established with authors such as Castilho (2011), D'Ambrósio (1998), Silva (2017), Dussel (2005), Quijano (2005, 2020), Munanga (1995/1996), Arroyo (2013), among others. Methodologically, this is a qualitative study, in which ethnography based on Geertz (2008), and action research, based on the precepts of Thiollent (1986). Four stages were performed during the development of the action research: study of texts on the assumptions of Ethnomathematics with the participating teachers; field research carried out by the teachers to survey the mathematical knowledge in the community; elaboration, by the teachers, of a pedagogical activity using the information gathered in the field research; and the application of the teachers' pedagogical activity with the students at the community schools. The data collection tools used were participant observation, semistructured interviews, questionnaire, and document analysis. The results showed, based on the reports of the participating teachers, that the studies on the assumptions of Ethnomathematics, the field research to gather the knowledge of the communities and the application of the pedagogical activity with this knowledge with the students during the action research stages, contributed to the understanding of the importance of establishing a dialogue between the knowledge of the quilombola community and the knowledge of the schools. Meeting the research objective, the teachers' reports affirmed that it is possible to be based on the assumptions of Ethnomathematics during the teaching of mathematics in quilombola schools.